Awareness, knowledge and attitude toward colorectal cancer among students in Universiti Tunku Abdul Rahman (UTAR), Kampar, Perak - Lim, Peh Nee (2023)
The incidence of colorectal cancer (CRC) ranks third among all cancers worldwide. Colorectal cancer was the second most common cancer in Malaysia between 2012 and 2016, accounting for 13.5% of new cases. Due to nutrition, environmental, and lifestyle changes, young people were diagnosed with advanced CRC at a higher rate. Lack of CRC awareness and information delays diagnosis. The aim of this study was to determine the awareness, knowledge of CRC and attitude about colorectal cancer screening (CRCS) among students from Universiti Tunku Abdul Rahman, Kampar, Perak. Seven sections of a survey questionnaire that were taken from pertinent literature were administered as part of the study process. Utilizing SPSS for data analysis, tests including the Mann-Whitney U and Kruskal Wallis tests were used to evaluate differences in awareness, knowledge, and attitude (AKA) according to sociodemographic factors. Pearson's Chi-square test and Fisher Exact test were used to examine the relationship between sociodemographic variables, CRC incidence age knowledge, and warning signs knowledge and confidence in CRC warning sign iii detection. Most of the 196 respondents had good awareness (47.4%), warning indicators knowledge (49.5%), and a positive attitude (59.2%). However, 38.3% of respondents knew nothing about CRC risk factors. In the study population, females had significantly higher awareness, warning sign knowledge, risk factor knowledge, and CRCS attitude scores than males (p = 0.014; p = 0.004; p = 0.001; p = 0.016). Additionally, health science students had a considerably higher AKA score (p < 0.001 for all variables). Significant differences were seen between age groups in understanding warning indicators (p = 0.004) and risk factors (p < 0.001). Higher education levels were associated with higher awareness, knowledge, and risk factor scores (p = 0.002, p = < 0.001). Better monthly income respondents scored better on knowledge (p = 0.043; 0.012) and attitude (p = 0.004). Except for warning sign knowledge, CRC family history was associated with higher AKA scores (p = 0.007; p = 0.015; p = 0.001; p = 0.036). Only 10% were very confident in warning sign detection. CRC incidence age knowledge was correct for about 40% of respondents. Gender, age, and study field significantly affected warning sign detection confidence. Age, year of study, monthly income, and CRC family history were correlated with age-related CRC incidence knowledge. The majority of respondents in this study had a good awareness of CRC, good knowledge of CRC warning signs, and a positive attitude toward CRCS, but their knowledge of risk factors was poor, indicating that CRC risk factor education and information should be greatly promoted, especially in males and those under 20 years old, from non-health science background, lower year of study, lower monthly income, and without CRC family history